Formative Decision-Making in Response to Primary Science Classroom Assessment: What to do Next? - Earle, Sarah (Frontiers in Education, 2021)
Classroom assessment is purposeful when the information is utilised by teachers to support learning. Such formative assessment practices can be difficult to enact in a primary science classroom, with the whole class often involved in practical activities and with limited lesson time. This preliminary study seeks to explore formative decision-making and the subsequent actions taken by teachers in the classroom. Primary teachers who used a Teacher Assessment in Primary Science (TAPS) Focused Assessment activity were asked to describe what action they took as a result of the classroom interactions stimulated by the activity. 142 teachers in 9 regions of England completed a paper questionnaire at a training day. The qualitative data pertinent to the study was extracted and thematic content analysis carried out to determine the kinds of actions and changes to practice that were described. It was found that the ‘next step’ described by teachers varied in timing; some made changes within the lesson, others provided follow up activities or made longer-term adaptation to teaching practices. Being responsive to the assessment information provided by the children took many forms, for example, supporting pupils to reflect on investigations during the lesson, discussing vocabulary or concepts, providing time for further exploration, or explicit modelling of science skills. Formative decisions were taken at a whole class level, rather than making individual adaptations. It is argued that enabling teachers to be more explicit about their tacit decision-making could support them to make more formative use of assessment information to support pupil learning.